Climate-Induced Evolution of the Behaviour and Life-History Strategies of Atlantic Cod (Gadus morhua). A Modelling Approach - Holt, Rebecca (The University of Bergen, 2015)
Climate change influences the marine environment, with ocean warming being the foremost driving factor governing changes in the physiology and ecology of fish. At the individual level temperature can directly influence numerous physiology processes in marine fish as well as bioenergetics, having consequences for life-history processes and population level consequences. A primary mechanism through which temperature can affect fish is through respiratory physiology as it has consequences for performance and fitness. The difference between maximum metabolic rate and standard metabolic rate is referred to as aerobic scope, and is suggested to constitute a key limiting process prescribing how fish may cope with or adapt to climate warming. Field data and experiments have demonstrated an array of effects and influences of temperature on Atlantic cod and other marine fish species. This PhD research explores how temperature can influence the life-history and behaviour of Atlantic cod through a theoretical modelling approach. A state-dependent energy allocation model was developed to predict temperature-induced adaptations for the life-histories and behaviour of Atlantic cod, in response to climate warming. The model was parameterised primarily for the North-East Arctic cod stock and then extended to facilitate parametrisation of a further 19 stocks, enabling intra-specific stock comparisons across the North-Atlantic. The model is based on life-history theory, which addresses how an individual should schedule its life to maximise its expected lifetime reproductive output. Energy allocation and investment into growth, maturation and reproduction depends on a number of physiological and ecological factors, such as respiratory physiology and aerobic scope, constraints on body size, environmental variability in prey availability, spawning migration distance, and mortality. These constraints and mechanisms are well justified to the physiology and ecology of the species. By using state-dependent dynamic programming techniques, ...